Impacts of COVID-19 on Myanmar’s poultry sector: Implications for achieving the sustainable development goals - Fang, Peixun; Belton, Ben; Zhang, Xiaobo; Ei Win, Hnin (International Food Policy Research Institute, 2020)
This paper analyzes the impact of COVID-19 on two types of poultry production systems, broilers and layers, in Myanmar using five waves of telephone surveys from June to August 2020. The surveys were implemented with 269 poultry farms previously surveyed in 2019. The slow supply response of layer farms to increased egg demand after the initial COVID-19 shocks has resulted in higher egg prices for consumers. This, in turn, has affected nutritional intake, making it more difficult for Myanmar to achieve the second Sustainable Development Goal of ending hunger and malnutrition by 2030. Within both broiler and layer production systems are found both integrated poultry and fish farms and pure poultry farms. For layer farms, integration of poultry production with fish has provided a buffer against risk; the bankruptcy rate among integrated layer-fish farms was much lower than among pure layer farms. However, such advantages of integration of poultry with fish production are not seen for broiler farms.